Solitary Bone Plasmacytoma of Humerus Presenting as a Nonhealing Fracture in a Child: A Rare Entity. Issue 1 (15th January 2022) - Tandon, Sneha; Khanna, Nehal; Chivate, Rahul; Dey, Sayak; Gulia, Ashish; Narula, Gaurav; Shah, Sneha; Rane, Swapnil; Banavali, Shripad; Laskar, Siddharth
Abstract : Solitary bone plasmacytoma is an extremely rare entity and is characterized by localized proliferation of monoclonal plasma cells. Plasmacytomas are extremely rare in the pediatric population. The median age at diagnosis is usually the fifth or sixth decade, with axial skeleton being more commonly involved than appendicular. We hereby, report the case of a 13-year-old boy with solitary bone plasmacytoma of the right humerus. Though extremely rare in the pediatric age group, plasmacytomas may be considered as one of the remote differentials in children presenting with solitary bone tumors.